Electric discharge evidence found in a new class of material in the Chicxulub ejecta - Kletetschka, Gunther; Ocampo Uria, Adriana; Zila, Vojtech; Elbra, Tiiu (Scientific reports, 2020)
Chicxulub impact (66 Ma) event resulted in deposition of spheroids and melt glass, followed by deposition of diamectite and carbonate ejecta represented by large polished striated rounded pebbles and cobbles, henceforth, called Albion Formation1 Pook’s Pebbles, name given from the first site identified in central Belize, Cayo District. Here we report that magnetic analysis of the Pook’s Pebbles samples revealed unique electric discharge signatures. Sectioning of Pook’s Pebbles from the Chicxulub ejecta from the Albion Formation at Belize showed that different parts of Pook’s Pebbles had not only contrasting magnetization directions, but also sharply different level of magnetizations. Such behavior is indicative of electric discharge taking place sometimes during the formation of the Chicxulub ejecta blanket. In addition, some of the Pook’s Pebbles’ surface had recrystallized down to 0.2 mm depth. This is evidence of localized extreme pressures and temperatures during the fluidized ejecta formation which was imprinted in the outer layer of Pook’s Pebbles. Recrystallization caused formation of nanophase iron along the surface, which was revealed by mapping of both natural remanent magnetization and of saturation remanence magnetization signatures. While the spheroids’ magnetization orientation is consistent with reversed magnetic field at the time of impact, the study of the Pook’s Pebbles provided, in addition, new evidence of electric charging during the vapor plume cloud processes.